2002
DOI: 10.1038/nsb823
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a laccase from Melanocarpus albomyces with an intact trinuclear copper site

Abstract: We have crystallized the ascomycete laccase from Melanocarpus albomyces with all four coppers present and determined the crystal structure at 2.4 A resolution. The enzyme is heavily glycosylated and consists of three cupredoxin-like domains, similar to those found in the Cu-depleted basidiomycete laccase from Coprinus cinereus. However, there are significant differences in the loops forming the substrate-binding pocket. In addition, the crystal structure of the M. albomyces laccase revealed elongated electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
278
1
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(308 citation statements)
references
References 31 publications
20
278
1
9
Order By: Relevance
“…CueO can oxidize a range of substrates in vitro, including catechols, siderophores, and Fe(II) (10), and this activity is greatly enhanced in the presence of excess (ϳ100 M) copper(II) ions (10,15), suggesting that binding of a labile copper is important for enzymatic activity. We recently determined the crystal structure of CueO at 1.4-Å resolution (15) and showed that its structure is similar to that of other multicopper oxidases, such as ascorbate oxidase (16) and several laccases (17)(18)(19). As expected, CueO contains a T1 "blue copper" site, near the point at which the larger substrate is believed to bind, as well as a trinuclear copper center, where oxygen reduction occurs.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…CueO can oxidize a range of substrates in vitro, including catechols, siderophores, and Fe(II) (10), and this activity is greatly enhanced in the presence of excess (ϳ100 M) copper(II) ions (10,15), suggesting that binding of a labile copper is important for enzymatic activity. We recently determined the crystal structure of CueO at 1.4-Å resolution (15) and showed that its structure is similar to that of other multicopper oxidases, such as ascorbate oxidase (16) and several laccases (17)(18)(19). As expected, CueO contains a T1 "blue copper" site, near the point at which the larger substrate is believed to bind, as well as a trinuclear copper center, where oxygen reduction occurs.…”
mentioning
confidence: 97%
“…The copper atoms of the trinuclear center lie in nearly identical positions in the previous and present structures; however, in the present structure, modeling of the bridging atom as a single oxygen resulted in a low temperature factor (3 Å 2 ) and a 5 residual electron density peak, indicating the need for more electrons at this site. The density is clearly spherical, and modeling as dioxygen, as was done in the structure of laccase from Melanocarpus albomyces (19), resulted in an unsatisfactory refinement. Modeling the atom as chlorine (10 mM CuCl 2 was added to the crystal), refined well, yielding copper-tochlorine distances of 2.3 and 2.5 Å (unrestrained), similar temperature factors for copper and chlorine atoms (ϳ20 Å 2 ), and no residual electron density.…”
Section: Structural Studies Location Of Labile Copper-optimalmentioning
confidence: 99%
“…MCOs use a minimum of four Cu centers: a ''blue,'' type 1 Cu site and a trinuclear Cu cluster composed of a ''normal,'' type 2 Cu and a binuclear type 3 Cu site that together catalyze the 4-electron reduction of O 2 to water with concomitant oxidation of substrates (2,3). Crystal structures indicate that both the type 3 Cu active sites in Hc/CatO/Tyr (4-10) and the MCOs (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) are similarly held in the protein by three His ligands on each Cu center. No additional ligands are present in the deoxy forms, whereas oxygen-derived ligands bridge and exchange couple the two Cu(II)s in the oxidized forms.…”
mentioning
confidence: 99%
“…This was also observed in the crystal structure of laccase from M. albomyces (Hakulinen et al, 2002). It is well known that the Cu2 ion is involved in the transformation of reduced oxygen to water molecules (O 2 À + 2H + ?…”
Section: Trinuclear Centermentioning
confidence: 56%